The Constitutional Court and science: some trends and milestones (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
What novelties are emerging in the Court’s attitude to judging science-based laws? Are there similarities with other trends taking place even in different areas of the legal system? The essay identifies some obvious constants in the constitutional jurisprudence on the subject, while pointing out the contrasts with the different options put forward in the resolution of some discussed and “sensitive” cases. In particular, there emerges an attitude of the Court somewhat in favor of solutions calibrated to the cases and persons involved, as opposed to solutions of quite a different nature (which, however, continue to emerge mainly in legislation and, albeit sporadically, also in constitutional jurisprudence).
Keywords: Constitutional Court; Legislature; scientific data; reasonableness; balancing